A first candidate in principle to resolve or dissolve conflicts - Pereda, Carlos (Estudios de Filosofía, 2008)
There is no doubt, there have been and are many and very different cultures or, if you prefer, because cultures are usually constituted and deployed over time, many and very different traditions. However diffuse their limits and however vague their ways of organizing themselves internally, to some degree, each culture, each tradition, conditions and, not infrequently, even shapes what the members of one or more societies, even in very long periods. periods, they want, believe, feel, hope... and, consequently, act. However, what are some of the most persistent effects of this multiplicity of cultures, of traditions: of the so loudly applauded, and also no less loudly lamented multiculturalism?